PENERAPAN METODE TAHSIN DAN TAJWID DALAM PEMBELAJARAN AL-QUR’AN SISWA KELAS 7 TAHFIDZUL QUR’AN PONDOK PESANTREN AL-IKHLASH BEKONANG 2023 - Abdullah Nashir, Jundi; Subando, Joko; Effendi, Arif (QATHRUNÂ, 2023)
This study aims to describe the application of the tahsin and tajwid methods in learning the Qur'an, as well as the supporting and inhibiting factors for the application of the tahsin and tajwid methods in learning the Qur'an. This study uses a qualitative method. Data collection methods used were observation, observation guidelines, interviews, interview guidelines and documentation. The data analysis technique is carried out through four stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the application of the method applied at the Tahfidzul Qur'an Al-Ikhlash Bekonang Islamic Boarding School in learning the Qur'an is to apply two learning models, namely learning in the classroom and outside the classroom. Supporting factors for the tahsin and tajwid methods in class 7 Al-Qur'an learning at the Al-Ikhlash Bekonang Sukoharjo Islamic Boarding School in 2023 are divided into 2, supporting factors in the classroom, namely: a planned system, teacher quality, as well as motivation and appreciation, as well as supporting factors in outside the classroom, namely: choosing the right method, the atmosphere of the Islamic boarding school environment, and the teacher's attention. The inhibiting factors of the tahsin and tajwid methods in learning the Qur'an for grade 7 students at the Al-Ikhlash Bekonang Sukoharjo Islamic Boarding School in 2023 are divided into 2 inhibiting factors in the classroom, namely: not serious in learning and not good friendship, and inhibiting factors outside class, namely: lack of interest in learning and poor mental state (bad mood).